2018
DOI: 10.1055/s-0038-1673415
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Function in Patients with Severe and Moderate Haemophilia A and B

Abstract: The life expectancy of patients with haemophilia has increased and therefore the interest in age-related comorbidities has grown. The aim of this study was to determine whether haemophilia patients have a different endothelial function compared with the general population. A total of 26 patients with severe or moderate haemophilia A or B, 14 controls and 36 patients with coronary artery disease (CAD) were included in this study. Five markers of endothelial dysfunction (MOEDs) were determined. Moreover, the end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
18
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(30 citation statements)
references
References 28 publications
(40 reference statements)
10
18
2
Order By: Relevance
“…The high expression of miRNA-155 in CAD and haemophilia patients are consistent with the significantly elevated sICAM-1 levels in haemophilia patients in our previous study. 2 and the positive correlation between miRNA-155 and sICAM-1 as described earlier. This outlines the involvement of miRNA-155 and miRNA-21 in pro-inflammatory processes leading to atherosclerosis by upregulations of VCAM-1, ICAM-1 and MCP1 through targeting different pathways.…”
Section: Discussionsupporting
confidence: 63%
“…The high expression of miRNA-155 in CAD and haemophilia patients are consistent with the significantly elevated sICAM-1 levels in haemophilia patients in our previous study. 2 and the positive correlation between miRNA-155 and sICAM-1 as described earlier. This outlines the involvement of miRNA-155 and miRNA-21 in pro-inflammatory processes leading to atherosclerosis by upregulations of VCAM-1, ICAM-1 and MCP1 through targeting different pathways.…”
Section: Discussionsupporting
confidence: 63%
“…Indeed, abnormal endothelial function was recently recognized in patients with hemophilia. 23 Our current findings will inspire future investigations looking at the molecular mechanism underlying loss of endothelial fenestration associated with FVIII deficiency and whether or how this possibly could be affecting liver gene therapy in hemophilia.…”
Section: Resultsmentioning
confidence: 79%
“…In our study a lower than expected number of CVD events was observed. From previous studies it is known that haemophilia does not protect against atherosclerosis 6,[22][23][24] . We hypothesized that lower clotting factor levels diminish pathologic clot formation at sites of unstable plaques in PWH.…”
Section: Discussionmentioning
confidence: 99%